KARET LEMBARAN YANG TERBUAT DARI CAMPURAN SERBUK BAN BEKAS DAN KARET ALAM YANG DISETARAKAN DENGAN SIR-20 UNTUK PEMBUATAN SOL SEPATU OLAH RAGA - Tumanggor S, Ojakma; Dharma S, Anwar; Marlianto, Eddy (JURNAL IKATAN ALUMNI FISIKA, 2016)
The study of waste tires powder processing as a filler on making shoe sole has been done. On the research, it has been found the vulcanizate technical on natural rubber of shoe sole by using waste tires powder and was compound to the tecto the technical specification of shoeÂ  sole according to IndonesiaÂ  Natural Standard. The process of making waste tires powder triller 60 mesh particle size has been done by steps of procces, producing of particle size, washing, drying and screening. The vulcanizate of natural rubber shoe sole wich contained waste tires powder and using press molding technical at 1800 for 4,50 minutes. The result of the research showed that the vulcanizate of shoe sole natural rubber containing waste tires powder triller 60 mesh could be used to manufacturing sport shoe sole because its vulcanizate had enough technical process accoording to Indonesia National Standard 06-1844-199 Ed 1.2